2012
DOI: 10.1097/wnf.0b013e31827172e5
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Pharmacotherapy in the Treatment of “Internet Addiction”

Abstract: The advent of the Internet is among the most significant changes in recent decades and has greatly affected the entire range of human experience. However, it has, in turn, led to the emergence of psychopathological features of addiction linked to its use. Literature on the clinical management of the distress related to Internet use systematically measures up to an evolving nosography, with ambiguous definitions of the phenomenon and a diversity of diagnostic, prognostic, and therapeutic criteria. To date, case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 56 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…Even though not all manuscripts have explained the treatment outcome, we believe it is necessary to reveal how this model of intervention works, increasing this information to health professionals that treats this demand. We also recommend a review of the literature on the pharmacological aspect in the treatment of these addicts 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Even though not all manuscripts have explained the treatment outcome, we believe it is necessary to reveal how this model of intervention works, increasing this information to health professionals that treats this demand. We also recommend a review of the literature on the pharmacological aspect in the treatment of these addicts 73 .…”
Section: Discussionmentioning
confidence: 99%
“…A later study by Han and Renshaw (2012) showed that bupropion reduced Internet addiction scores, mean time of online game playing, and Beck Depression Inventory (BDI) scores in a group with comorbid excessive online video game playing (EOP) and Major Depressive Disorder (MDD). For review of existing pharmacological treatment for IAD, see Camardese, De Risio, Di Nicola, Pizi, and Janiri (2012).…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Some studies have already demonstrated some associations with molecular genetic markers (for an overview see Montag and Reuter, 2015a,b) and also psychopharmacological approaches have been put forward (see overviews Camardese et al, 2012, 2015). Among others, these studies yielded evidence for a role of dopaminergic and serotonergic systems in Internet addiction, and of course dopamine has been implicated in all addiction.…”
Section: Introductionmentioning
confidence: 99%